2022
DOI: 10.1029/2022gl098148
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Forcing of the Pacific Meridional Mode: Tropical Pacific‐Driven Versus Internal Variability

Abstract: The Pacific Meridional Mode (PMM) impacts tropical Pacific sea surface temperature variations, which in turn affect the PMM through the excited atmospheric teleconnections. Previous studies linked this loop to the tropical Pacific‐excited North Pacific Oscillation (NPO; the second empirical mode of North Pacific sea level pressure variability), while a recent study proposed the linkage to the excited Aleutian low (AL) variability (the first empirical mode). Unraveling their relative importance for the loop is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Here we identify that the PMM mechanism (emphasizing its crucial role) is more important than the OHC mechanism in generating multi-year LN events. The PMM mechanism not only influences tropical Pacific variability and triggers ENSO events but can also be triggered by ENSO events 9 , 10 , 44 , 45 , leading to another ENSO event with the same phase and resulting in a multi-year event 9 12 , 17 , 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Here we identify that the PMM mechanism (emphasizing its crucial role) is more important than the OHC mechanism in generating multi-year LN events. The PMM mechanism not only influences tropical Pacific variability and triggers ENSO events but can also be triggered by ENSO events 9 , 10 , 44 , 45 , leading to another ENSO event with the same phase and resulting in a multi-year event 9 12 , 17 , 46 .…”
Section: Resultsmentioning
confidence: 99%
“…For convenience, when the pattern has negative SLP anomalies to the south and positive to the north, it is defined as the positive NPO phase. Previous studies have suggested that the ENSO can influence the NPO [55][56][57][58] . To minimize the possible simultaneous ENSO impact on NPO, we linearly removed the ENSO signal 59,60 , which is represented by the Niño3.4 index, from both NPO and circulation fields, before conducting further analyses.…”
Section: Observational Analysis and Definitionsmentioning
confidence: 97%
“…In these studies, the PMM‐ENSO connection is a one‐way relationship (i.e., the PMM influences ENSO). Whereas recently, more and more investigations have pointed out that the preceding ENSO‐related SST anomaly in the central tropical Pacific (CTP) can in turn promote the occurrence and development of an in‐phase PMM event by exciting poleward atmospheric wave responses (Di Lorenzo et al., 2015; Fan et al., 2023; Fang & Yu, 2020; Stuecker, 2018; Yeh et al., 2018; Zhang et al., 2022). Now then, PMM events can accordingly be divided into two types: “stochastic” events forced by occasional extratropical atmospheric anomalies and “successive” events forced by ENSO‐related tropical SST anomaly.…”
Section: Introductionmentioning
confidence: 99%